International Journal of Nursing Education Scholarship (De Gruyter, 2004)
The International Journal of Nursing Education Scholarship (IJNES) publishes significant research and scholarship in the broad field of nursing education. The mandate of the journal is to present high quality papers to advance nursing education through research, description of innovative methods, or introduction of novel approaches about all aspects of nursing education in a timely manner.